Comparative Analysis of Normal versus Fetal Growth Restriction in Pregnancy: The Significance of Maternal Body Mass Index, Nutritional Status, Anemia, and Ultrasonography Screening. (29th December 2013) - Sawant, Laxmichaya D.; Venkat, Shirin
Abstract : Fetal growth restriction or intrauterine growth restriction is one of the leading causes of perinatal mortality and morbidity in newborns. Fetal growth restriction is a complex multifactorial condition resulting from several fetal and maternal disorders. The objective of this study was twofold: first to examine the correlation between maternal parameters such as body mass index (BMI), nutritional status, anemia, and placental weight and diameter, and their effects on fetal growth and then to evaluate the effect of early screening by ultrasonography (USG) on the outcome of growth restricted pregnancies. In this study, 53 cases of fetal growth restriction were compared to 53 normal fetuses delivered in consecutive sequence. Growth restricted fetuses were delivered earlier in gestation, when compared with normal growth fetuses. Maternal anemia and malnutrition have significant association with the fetal growth restriction. Maternal anthropometry, such as low BMI, had effects on placental diameter and weight, which, in turn, adversely affected fetal weight. Thus, early USG screening along with robust screening for maternal BMI, nutritional status, and anemia can assist the obstetric team in providing early diagnosis, prompt intervention, and better outcome in pregnancy with fetal growth restriction.